Britain’s First Labour Government - Shepherd, J. author. aut Link
XII, 255 p.
Keywords: This volume is the first major account for nearly fifty years to critically re-assess Labour's first period in office in terms of domestic, foreign and imperial policy. It draws on a wide range of private papers and official sources and reconstructs the history of this forgotten government in the broader social and political context of the 1920s.